1992
DOI: 10.1002/mrd.1080330209
|View full text |Cite
|
Sign up to set email alerts
|

F‐actin in guinea pig spermatozoa: Its role in calmodulin translocation during acrosome reaction

Abstract: The presence of actin has been determined in mammalian spermatozoa. However, its function in these cells is still almost unknown. Only in boar spermatozoa has evidence for F-actin and a possible function for it been presented. In this work, actin distribution and F-actin were determined in uncapacitated, capacitated, and acrosomal-reacted guinea pig spermatozoa, by means of monoclonal and polyclonal antibodies, using an indirect immunoperoxidase technique, and by the use of rhodamine-phalloidin. With the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 34 publications
3
45
0
2
Order By: Relevance
“…Actin has been detected immunologically also in spermatozoa from various species, including bovine spermatozoa [11]. It has been proposed that actin could play a role in the stabilization of the acrosome structure [12] but no direct involvement of actin in sperm motility has been offered. To assess the occurrance of Rho proteins in bovine spermatozoa, spermaozoal membrane proteins and cytosolic proteins were ADP-ribosylated in the presence of [32p]NAD, and Rho proteins were visualized by autoradiography after SDS-PAGE.…”
Section: Introductionmentioning
confidence: 99%
“…Actin has been detected immunologically also in spermatozoa from various species, including bovine spermatozoa [11]. It has been proposed that actin could play a role in the stabilization of the acrosome structure [12] but no direct involvement of actin in sperm motility has been offered. To assess the occurrance of Rho proteins in bovine spermatozoa, spermaozoal membrane proteins and cytosolic proteins were ADP-ribosylated in the presence of [32p]NAD, and Rho proteins were visualized by autoradiography after SDS-PAGE.…”
Section: Introductionmentioning
confidence: 99%
“…This cytoskeleton is responsible for the clearance of integral membrane proteins from the peri-acrosomal plasma membrane, an event which seems critical for acrosomal exocytosis by mammalian spermatozoa (e.g. Moreno-Fierros et al, 1992) including those of man (Feuchter et al, 1986;Ochs et al, 1986;Benoff et al, 1996Benoff et al, , 1997aBenoff, 1997b). Subsequent conversion of polymerized actin (F-actin) to monomer actin (G-actin) apparently facilitates fusion of sperm plasma and outer acrosomal membranes.…”
mentioning
confidence: 99%
“…3, lane 2). Regarding the presence of gelsolin in the postacrosomal region and flagellum, our group has detected F-actin in both regions [Moreno-Fierros et al, 1992]. How gelsolin is involved in F-actin regulation in these regions will be the subject of future work.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the location of actin in the acrosomal region has been reported in the spermatozoa of several mammalian species [Talbot and Kleve, 1978;Camatini et al, 1986;Flaherty et al, 1988;Olson and Winfrey, 1991;Moreno-Fierros et al, 1992;Yagi and Paranko, 1995]. It has also been suggested that sperm cells must undergo actin filament depolymerization for AR to occur, due to the fact that, when actin depolymerization is inhibited by adding phalloidin to an isolated sperm membrane model [Spungin et al, 1995], membrane fusion is also hindered.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation